Hydrogeological investigations of river bed clogging at a river bank filtration site along the River Warta, Poland - Przybyłek, Jan; Dragon, Krzysztof; Kaczmarek, Piotr Michał Jan (Geologos, 2017)
River bank filtration (RBF) is a system that enriches groundwater resources by induced infiltration of river water to an aquifer. Problematic during operation of RBF systems is the deterioration of infiltration effectiveness caused by river bed clogging. This situation was observed in the Krajkowo well field which supplies fresh water to the city of Poznań (Poland) during and after the long hydrological drought between the years 1989 and 1992. The present note discusses results of specific hydrogeological research which included drilling of a net of boreholes to a depth of 10 m below river bottom (for sediment sampling as well as for hydrogeological measurements), analyses of grain size distribution and relative density studies. The results obtained have allowed the recognition of the origin of the clogging processes, as well as the documentation of the clogged parts of the river bottom designated for unclogging activities.